Effect of cross-sex hormone therapy on hematological parameters in transmen: A 1-year follow-up study - ÜSTAY, ÖZLEM (My University, 2023)
Objective: Testosterone is the primary cross-sex hormone therapy (CSHT) for the female-to-male (transmen) transition. However, there is a growing concern about the safety and long-term results of CSHT, including erythrocytosis and inflammation. We aimed to investigate the effects of testosterone therapy on hematological parameters and high-sensitive C-reactive protein (hsCRP) in transmen with a 1-year follow-up. Methods: This was a single-center prospective study in 45 hormone-naive transmen and 28 age-and body mass index (BMI)-matched ciswomen. Ciswomen were compared with hormone-naive transmen. Testosterone ester preparation (250 mg) was prescribed to all transmen every 21 days. The transmen were evaluated before treatment and 6 and 12 months following CSHT. Sex steroids, complete blood counts, and hsCRP were analyzed. Results: At initial assessment before CSHT, the transmen had higher total testosterone (P = .002), white blood cell count (P = .013), and neutrophil count (P = .015) than the ciswomen. The exogenous testosterone administration to transmen was associated with a significant increase in hematocrit (P < .001) and hsCRP (P = .002) at 12 months. Conclusion: Testosterone administration to transmen was associated with a significant increase in hematocrit and hsCRP at 12 months. These parameters should be regularly monitored in line with current guidelines.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Geriatri; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Geriatrics; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; TIP, GENEL & DAHİLİ; GERİATRİ ve GERONTOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ENDOCRINOLOGY & METABOLISM; MEDICINE, GENERAL & INTERNAL; GERIATRICS & GERONTOLOGY; Geriatri ve Gerontoloji; Dahiliye; Endokrinoloji, Diyabet ve Metabolizma; Geriatrics and Gerontology; Internal Medicine; Endocrinology, Diabetes and Metabolism; ciswomen; cross-sex hormone therapy; hematocrit; hematological parameters; testosterone; Transmen